STRENGTHENING THE RESEARCH OF KEY ENABLING TECHNOLOGIES FOR NEW INNOVATIONS - Sanja Tišma; Karolina Horvatinčić; Iva Tolić; Anamarija Farkaš (Economic Review)
The development of science and technology in recent times is hosting major changes with the emergence of new key concepts, e.g. nanotechnology, micro nanoelectronic, etc. Technologies are changing the way in which society operates and there is a need to ensure that they are used in a best possible way. The way to address these new concepts is crucial for achieving economic and social prosperity and an obvious indicator of a country's ability to maintain a sustained growth in accordance with the latest advances. In Croatia, key enabling technologies (KETs) are recognized as one of the two cross-cutting topics able to create the biggest addedvalue and foster the emergence of new economic activities, the rising of the productivity of the Croatian economy and the creation of new and sustainable job opportunities in the Croatian Smart Specialization Strategy. In addition, Croatian scientific and research institutions have a lot of experience in KET-related projects funded by the European Union, either as a partner in international projects or having their own project. The biggest Croatian stren-gth in KET are open economy and relatively high-level of internationalisation of national companies, as well as the access to a pool of high-skilled workers and good quality infra-structures with substantial investments in the fields of transportation, telecommunications and energy. However, there is limited colla-boration between industry and academia in R&D and there is a need to further support and train SMEs.